Adaptive Time Management Strategies in Surgical Residency Education: A Qualitative Study in a Teaching Hospital in Manado - Andriessanto C. Lengkong; Harol R. Lumapow; Joulanda A M Rawis; Jeffry Sony Junus Lengkong (International Journal of Information Technology and Education, 2026)
Surgical residency education places learners in an unusually demanding learning environment in which clinical care, academic responsibility, operative exposure, research tasks, documentation, and personal recovery compete for limited time. This article analyzes adaptive time management strategies used by surgical residents in a teaching hospital in Manado and formulates a contextual model for supporting professional learning and resident well-being. The study used a qualitative descriptive approach with in-depth interviews, observation, and documentation involving surgical residents, clinical supervisors, and a residency education coordinator. Thematic analysis identified three interrelated dimensions of time management: planning, implementation, and evaluation. Planning was characterized by adaptive daily prioritization, clinical urgency mapping, and individualized self-management tools. Implementation was characterized by flexibility in response to emergency cases, teamwork, micro-learning during clinical gaps, and adjustment to unpredictable clinical rhythms. Evaluation was carried out through personal reflection, peer feedback, and supervisor input, although institutional monitoring remained limited. The findings show that time management is not merely a technical scheduling activity but a professional self-regulation competence shaped by workload, clinical pressure, team culture, institutional support, and adult learning experience. The article proposes an adaptive-reflective time management model that integrates strategic clinical prioritization, flexible time blocking, integrated clinical learning, reflective practice, supervisor coaching, and system-level policy feedback. The model contributes to clinical education management by positioning time management as a humanistic and sustainable strategy for improving learning effectiveness, professional identity formation, and resident well-being.